EMBEDDED WH-QUESTIONS IN L2 ENGLISH IN INDIA: Inversion as a main clause phenomenon. Issue 1 (27th August 2014) - Stringer, David
Abstract : This corpus study brings a second language (L2) research perspective, insights from generative grammar, and new empirical evidence to bear on a long-accepted claim in the World Englishes literature—namely, that inversion with wh -movement in colloquial Indian English is obligatory in embedded clauses and impossible in main clauses. It is argued that this register of Indian English is a L2 variety, functioning as part of a multilingual code repertoire, but that syntactic universals apply to first and second languages alike. Despite recent attempts at formalization, this distribution should be unattested, as such a grammar would fall outside the constraints of Universal Grammar and would contradict proposed discourse-pragmatic principles of natural language. A Perl program was created to search the Indian subcorpus of the International Corpus of English (Greenbaum, 1996 ) for relevant distributional patterns. Results reveal that wh -inversion in Indian English operates in the same way as in other varieties: It is robustly attested in main clauses and appears only occasionally in embedded clauses where syntactic and pragmatic conditions allow; it is obligatory only with interrogative complementizer deletion. Thus, contrary to the standard account but commensurate with recent corpus studies, users of English in India exhibit knowledge of universal constraints in this domain.